NEW HEURISTICS FOR THE NO-WAIT FLOWSHOP WITH SEQUENCE-DEPENDENT SETUP TIMES PROBLEM - Araújo, Daniella Castro; Nagano, Marcelo Seido (Brazilian Journal of Operations & Production Management, 2015)
In this paper, we address the problem of scheduling jobs in a no-wait flowshop with sequence-dependent setup times with the objective of minimizing the makespan and the total flowtime. As this problem is well-known for being NP-hard, we present two new constructive heuristics in order to obtain good approximate solutions for the problem in a short CPU time, named GAPH and QUARTS. GAPH is based on a structural property for minimizing makespan and QUARTS breaks the problem in quartets in order to minimize the total flowtime. Experimental results demonstrate the superiority of the proposed approachs over three of the best-know methods in the literature: BAH and BIH, from Bianco, Dell´Olmo and Giordani (1999) and TRIPS, by Brown, McGarvey and Ventura (2004).